Pathways to Criminal Hacking: Connecting Lived Experiences with Theoretical Explanations - Melissa Martineau; Elena Spiridon; Mary Aiken (Forensic Sciences)
Background: Over the course of the last decade, cybercrime has become a significant global concern. A comprehensive approach to crimes that occur in cyber contexts needs to address not only the technological aspects of cybercrime but also the human elements. Therefore, the aim of the current research is twofold: first, to gain an in-depth understanding of the pathways that lead to criminal hacking behavior through interviews with current or former criminal hackers, and second, to explore how the lived experiences of these individuals fit within theoretical explanations of hacking. Method: Semi-structured interviews were conducted with a sample of ten current and former criminal hackers. Participants for this study were recruited through social media and hacker forums. Interviews were conducted from November 2023 to March 2024. Data collected during the interviews were analyzed through a process of thematic analysis. Focusing on the lived experiences of these hackers, a “pathway of hacking” behavior, expanding upon those proposed in research emanating from Europe, was identified. Findings: Notably, the current study found that young males who are curious and creative in childhood, experience destabilizing events, and develop an early interest in technology are well placed to follow the pathway to criminal hacking behavior. Online gaming was identified as a possible gateway to criminal hacking activities. A sense of overcoming a challenge, being elite, and having “control over the machine” encourages youth to continue criminal hacking activities. In addition to the identification of a criminal hacking pathway, an integration of existing cyberpsychological, psychological, criminological, and sociological theories is presented to provide a theoretical explanation for the initiation, continuation, and desistence of criminal hacking behavior. This work represents the first effort to present an integration of theories (e.g., Social Learning, General Theory of Crime, Flow, and the cyberpsychological theoretical construct of the “Online Disinhibition Effect”) based on the stages of the criminal hacking pathway.